2016
DOI: 10.1016/j.ijsu.2016.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of hepatobiliary scintigraphy and ultrasound in the diagnosis of acute cholecystitis

Abstract: HIDA scan is superior to US as a diagnostic study in the setting of AC. Our current protocol of delayed HIDA (post-admission) was associated with increased TTS, LOS, and overall costs. Early confirmation with HIDA in high risk patients may hasten treatment allocation and improve outcomes in the setting of AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…HIDA scanning has sensitivities ranging from 91% to 92% compared with US, which has sensititives ranging from 26% to 73%. HIDA scanning has a specificity of 71%-79% compared with US, which has a specificity of 58%-80% (47)(48)(49).…”
Section: Acute Cholecystitismentioning
confidence: 99%
“…HIDA scanning has sensitivities ranging from 91% to 92% compared with US, which has sensititives ranging from 26% to 73%. HIDA scanning has a specificity of 71%-79% compared with US, which has a specificity of 58%-80% (47)(48)(49).…”
Section: Acute Cholecystitismentioning
confidence: 99%
“…The use of US in acute cholecystitis has been well reported, and its ease of use and non‐invasive modality have been described in case series studies . However, the diagnostic yield described in those articles varies according to the device, assessment criteria, and diagnostic criteria used in each of the studies, all of which were of small numbers of patients in single institutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnostic yield described in those articles varies according to the device, assessment criteria, and diagnostic criteria used in each of the studies, all of which were of small numbers of patients in single institutions. All studies that have compared the diagnostic yield of hepatobiliary scintigraphy (HIDA scanning) with that of US have found that the diagnostic yield is higher for HIDA scanning , but diagnostic imaging with US is nevertheless recommended in three newly proposed guidelines despite its limited diagnostic yield .…”
Section: Introductionmentioning
confidence: 99%
“…We designed our RIP after a thorough review of our historical data, in which we looked at the diagnostic performance of ultrasound for AC, perioperative data, and quality outcomes. For the latter study, we found that not only was US underperforming (sensitivity 26% for AC) but our classic approach was associated with delayed treatment [ 9 ]. However, the latter findings could not be attributed to poor management.…”
Section: Discussionmentioning
confidence: 99%
“…The features of the clinical feature score were determined by multivariate analysis of all presenting baseline clinical and laboratory findings in the historical group (n = 117). The details of this analysis have been previously described [ 9 ]. When all presenting features were analyzed, WBC count ≥10,000 (10 9 /L), glucose ≥140 (mg/dl), and age ≥50 years were the three presenting features that had a statically significant positive association with pathologically confirmed acute cholecystitis.…”
Section: Methodsmentioning
confidence: 99%